Undecorated Roman-Period Roof Tiles – An Old Material Providing New Results - Hamari Pirjo (Open Archaeology, 2023)
Undecorated ceramic roof tiles and their fragments are one of the most enduring and numerous remains of the earthen architecture of the Roman period to survive to us from many parts of the Roman world, especially from the Mediterranean region. Despite this, we have huge gaps in our knowledge regarding this material due to the sparsity in specialist studies and published excavation or survey records. The most detrimental gap is a lack of sufficiently fine-grained tile typology to easily situate and compare any tile material found. This work will outline the methodology used in the author’s recent research concerning Roman-period ceramic roof tiles in the Eastern Mediterranean and discuss the different ways we can approach undecorated roof tiles as material to gain valuable data. The work will also touch on the current limitation we have for further research in using this material as a dataset based on the status of research (limited and biased), the methodologies that would be most valid for research (e.g. is typology still a valid tool?), and the means we have in increasing the value of this material as a source for knowledge (better documentation). Such research allows us to gain meaningful and interesting new information on style, production, and transfer of knowledge and technology, which ultimately will help us to better understand how past societies functioned and interacted.